Answer: x² + (y + 9)² = 36
Step-by-step explanation:
Since we are given the endpoints of the circle, the midpoint between the two endpoints will be the center of the circle. The formula for determining midpoint of a line is
Midpoint = 1/2(x1 + x2), 1/2(y1 + y2)
The circle has a diameter with endpoints (6, -9)
and (-6, -9).
x1 = 6
x2 = - 6
y1 = - 9
y2 = - 9
= 1/2(6 - 6), 1/2(- 9 - 9)
= (0, - 9)
The diameter of the circle is the distance from the endpoint to another endpoint. To determine the diameter of the circle, we would apply The formula for determining the distance between two points on a straight line is expressed as
Distance = √(x2 - x1)² + (y2 - y1)²
Therefore,
Diameter = √(- 6 - 6)² + (- 9 - - 9)²
Diameter = √- 12² + 0² = √144
Diameter = 12
Radius = diameter/2 = 12/2 = 6
The center of the circle is (0, - 8)
The formula for determining the equation of a circle us expressed as
(x - h)² + (y - k)² = r²
Where
r represents the radius of the circle
h and k represents the x and y coordinates of the center of the circle. Comparing with the given points,
h = 0 and k = - 9
Radius, r = 6
Substituting into the formula, it becomes
(x - 0)² + (y - - 9)² = 6²
x² + (y + 9)² = 36